Barriers to accessing and utilising under-five primary health care services in Vhembe District - Livhuwani Tshivhase; Idah Moyo; Sophie M. Mogotlane; Sophy M. Moloko (AOSIS, 2024)
Background: Sub-Saharan Africa continues to be the region with the highest under-five mortality rate globally, with 74 deaths per 1000 live births. Even though under-five child primary health care (PHC) services are free in South Africa, accessing such services remains challenging. Children under 5 years reportedly die from common illnesses such as pneumonia, diarrhoea and malaria, which are treatable in PHC facilities. Aim: The study explored the barriers to accessing and utilising under-five PHC services in the Vhembe District. Setting: The study was conducted in two PHC centres in Vhembe District among guardians accessing care for under-five child health services. Methods: An interpretative phenomenology design was followed using a semi-structured individual interview guide. Sixteen participants were purposively sampled for the study. Colaizzi's steps of data analysis were followed, and trustworthiness as well as ethical principles were ensured throughout the study. Results: Four themes emerged as health system barriers, health personnel-related behaviours, health facility infrastructure barriers and guardians-related barriers. Subthemes emerged as distance from the facility, lack of resources, long waiting times; poor time management, lack of commitment and work devotion, insufficient waiting space; challenges with water and sanitation, guardians' healthcare beliefs and the urgency of the illness. Conclusion: It is imperative that an enabling professional and friendly environment is created to facilitate better access to PHC services for children under 5 years. Contribution: The study's findings brought insight into considering the context of the guardians in improving quality care for under 5 years.